The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1146/annurev-fluid-011212-140709
|View full text |Cite
|
Sign up to set email alerts
|

Leidenfrost Dynamics

Abstract: This review discusses how drops can levitate on a cushion of vapor when brought in contact with a hot solid. This is the so-called Leidenfrost phenomenon, a dynamical and transient effect, as vapor is injected below the liquid and pressed by the drop weight. The absence of solid/liquid contact provides unique mobility for the levitating liquid, contrasting with the usual situations in which contact lines induce adhesion and enhanced friction: hence a frictionless motion, and the possibility of bouncing after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
323
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(340 citation statements)
references
References 87 publications
7
323
3
1
Order By: Relevance
“…The aluminum surface was curved in order to keep drops stationary and suppress the buoyancy-driven Rayleigh-Taylor instability in the vapor layer. 4,10 Surprisingly, we found that all of the oscillation modes in Fig. 1 share the same azimuthal wavelength (λ ≈ 1.2 cm).…”
Section: The Many Faces Of a Leidenfrost Dropmentioning
confidence: 72%
“…The aluminum surface was curved in order to keep drops stationary and suppress the buoyancy-driven Rayleigh-Taylor instability in the vapor layer. 4,10 Surprisingly, we found that all of the oscillation modes in Fig. 1 share the same azimuthal wavelength (λ ≈ 1.2 cm).…”
Section: The Many Faces Of a Leidenfrost Dropmentioning
confidence: 72%
“…Recently [11], it was demonstrated that drops can rebound after impact on an extremely cold solid carbon dioxide surface (at -79°C, well below the limit of even homogeneous nucleation of water), because of the formation of a sublimated vapor layer acting both as impact cushion and thermal insulator, enabling drops to hover and rebound without freezing. A sublimating surface is different from aerodynamically assisted surface levitation [23][24][25] and from the Leidenfrost effect [12][13][14][26][27][28], in the sense that it is independent from liquid properties, such as boiling temperature, and there is no loss of drop mass due to its own boiling (as in the Leidenfrost phenomenon). Of course, in both cases an intervening layer is generated between the drop and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Richard et al 15 performed experiments showing that the contact time of a bouncing drop on a superhydrophobic surface is 2.6τ for high enough impact speeds, and that viscosity is not important in some regimes of droplet bouncing. Almost elastic collisions can also be achieved on a Leidenfrost surface or if a trapped air layer is preserved below the drop 16,17 .…”
Section: Introductionmentioning
confidence: 99%